1999
DOI: 10.1023/a:1008360323986
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel and cisplatin: An active regimen in patients with locally advanced, recurrent or metastatic squamous cell carcinoma of the head and neck

Abstract: The combination of docetaxel and cisplatin is feasible and active in locally advanced, recurrent, and metastatic squamous cell carcinoma of the head and neck.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 9 publications
3
48
0
3
Order By: Relevance
“…Docetaxel -cisplatin appeared to be a more effective combination, with overall response rates ranging from 33 to 76% (Kienzer et al, 1998;Schoffski et al, 1999;Specht et al, 2000;Glisson et al, 2002). In the trial conducted by the European Organisation for the Research and Treatment of Cancer (EORTC), docetaxel (100 mg m À2 ) plus cisplatin (75 mg m À2 ) produced a response rate of 54% (Schoffski et al, 1999). Of the 44 patients enrolled in this trial, 22 were chemotherapy-naïve and the response rate in this group was 86%.…”
Section: Potential Of Docetaxel In Scchnmentioning
confidence: 99%
See 1 more Smart Citation
“…Docetaxel -cisplatin appeared to be a more effective combination, with overall response rates ranging from 33 to 76% (Kienzer et al, 1998;Schoffski et al, 1999;Specht et al, 2000;Glisson et al, 2002). In the trial conducted by the European Organisation for the Research and Treatment of Cancer (EORTC), docetaxel (100 mg m À2 ) plus cisplatin (75 mg m À2 ) produced a response rate of 54% (Schoffski et al, 1999). Of the 44 patients enrolled in this trial, 22 were chemotherapy-naïve and the response rate in this group was 86%.…”
Section: Potential Of Docetaxel In Scchnmentioning
confidence: 99%
“…Of the 44 patients enrolled in this trial, 22 were chemotherapy-naïve and the response rate in this group was 86%. As with single-agent docetaxel, the main toxicity in each of the combination studies was myelosuppression (Kienzer et al, 1998;Schoffski et al, 1999;Colevas et al, 2000;Specht et al, 2000;Tubiana-Mathieu et al, 2000;Glisson et al, 2002). Mucositis was more commonly seen in the combination studies (particularly docetaxel -5-FU) than with single-agent docetaxel.…”
Section: Potential Of Docetaxel In Scchnmentioning
confidence: 99%
“…As an inhibitor of microtubule depolymerization, docetaxel is approximately twice as potent as paclitaxel, prompting many investigators to study its cytotoxicity in a variety of cell lines [25]. Further clinical studies have shown docetaxel to have potent anti-tumor activity against several human tumors, including ovarian [20], anthracycline-resistant breast [4,30], non-small cell lung [6,10,12] and head and neck squamous cell cancer [7,31]. However, its systemic use against CNS tumors has demonstrated no significant improvement in survival [9,29].…”
Section: Discussionmentioning
confidence: 99%
“…Its mechanism of action is through inhibition of tubulin depolymerization resulting in microtubule aggregation and cell death [33]. Docetaxel has shown efficacy in clinical trials against a variety of human tumors [4,6,7,10,12,20,30,31], as well as having been reported to act as a potent radiosensitizer against systemic malignancies [19,21,23,24]. In two Phase II trials, docetaxel showed no significant efficacy when given intravenously to patients with malignant glioma [9,29].…”
Section: Introductionmentioning
confidence: 99%
“…Grade 3 toxicities both hematologic and nonhematological were common. There were six complete responses (15%) and 16 partial responses (39%), resulting in an overall response rate of 54% in the intent-to-treat population [50].…”
Section: Docetaxel With Cisplatinmentioning
confidence: 99%